The Influences of Silent Reading Strategy Toward Students Reading Comprehension at SMAN 15 Muaro Jambi - Febriza, Ifran; Silfia, Efa; Dinata, Ridho Praja (Universitas Batanghari Jambi, 2024)
This research aims to find out whether there is any influence of silent reading strategy on students’ reading comprehension SMAN 15 Muaro Jambi. This research used a quantitative design with a quasi-experimental approach, including a quantitatively accepted pre-test and post-test. This research used total sampling namely population and sample of 34 people 17 students of Class XI A were selected as the control class and 17 students of Class XI B were selected as the experimental class. The technique of collecting data is by multiple choice questions in this research, the data analysis technique used the t-test (independent sample T-test) on the SPSS for Windows version 25 program. The results of this research indicate that Students’ reading comprehension in text taught using the silent reading strategy post-test the average count (mean) is 71.18 that value higher than the class using reading aloud to comprehend a narrative text in English subject namely the post-test average count (mean) is 62.06. and from data Analysis by Independent sample T Test t-count is 3.221 with the value t-table (2.369) by its result then Ho is rejected and Ha is accepted. The result of this study showed that there is an influence on the use of the Silent Reading Strategy towards students’ reading comprehension, and also it can be concluded that this silent reading strategy can applied in class besides that it helps a teacher increase Students’ reading comprehension in a text.